Phytoremediation by poplar: polyphenols polyamines and oxidative damage in the response to heavy metals in in vitro and in hydroponic cultures. - Tamanti, Fiorella <1958> (Alma Mater Studiorum - Università di Bologna, 2012)
Poplar is considered a good candidate for phytoremediation, but its tolerance to heavy metals has not been fully investigated yet. In the present work, two different culture systems (in vitro and aeroponic/hydroponic) and two different stress tolerant clones of Populus alba (AL22 and Villafranca) were investigated for their total polyphenol and flavonoid content, individual phenolic compounds, polyamine, lipid peroxidation and hydrogen peroxide levels in response to Cu. In AL22 poplar plants cultured in vitro in the presence or absence of 50 μM Cu, total leaves polyphenol and flavonoid content was higher in treated samples than in controls but unaltered in the roots. Equally the same clone, grown under aeroponic conditions and hydroponically treated for 72 h with 100 μM Cu, displayed increased amount of polyphenols and flavonoids in the leaves, in particular chlorogenic acid and quercetin, and no differences in the roots. In exudates from treated roots total polyphenols and flavonoids, in particular catechin and epicatechin, were more abundant than in controls. Polyamine levels show an increase in conjugated putrescine (Put) and spermidine (Spd) was found. In the Villafranca clone, treated with 100 μM Cu for 6, 24 and 72 h, the pattern of polyphenol and flavonoid accumulation was the same as in AL22; in Cu-treated roots these compounds decreased compared with controls while they increased in root exudates. Free polyamine levels rose at 24 and 72 h while only conjugated Put increased at 24 h. Cu-treated Villafranca plants exhibited a higher malondialdehyde production than controls indicative of membrane lipid peroxidation and, therefore, oxidative stress. An in vitro experiment was carried to investigate the antioxidant effect of the polyamine spermidine (Spd). Exogenous Spd, supplied together with 100 μM Cu, reduced the accumulation of polyphenols and flavonoids, MDA and hydrogen peroxide induced by Cu.